Face Threatening Acts of the Main Character in “The Half of it” Movie - Kadek Gita Arya Cahyaningrum; Gede Primahadi Wijaya Rajeg; I Nyoman Tri Ediwan (RETORIKA: Jurnal Ilmu Bahasa, 2022)
This study analyzed face threatening acts (FTAs) used by the main character in the movie titled The Half of It, focusing on (i) the types of the FTAs and (ii) how the FTAs are used by the main character. The data came from all utterances (words, phrases, clauses, sentences) produced by the main character. A pragmatic theory of FTAs from Brown and Levinson was applied to analyze the data qualitatively. Four types of FTAs are found in this study. The first type is “threatening the hearer’s negative face”, which was embedded in specific acts used by the main character, namely Suggestion, Threat, Reminding, Order, Warning, and Compliment. The second type is, “threatening the speaker’s negative face”, which is followed by such acts as Response to the hearer’s faux pas, Excuses, and Acceptance of offers. The third type is, “threatening the hearer’s positive face” with the acts of Criticism, Insults, Disagreement, Ridicule, Reprimand, Disapproval, Irreverence, Complaints, and Accusations. The last type of the FTAs is “threatening the speaker’s positive face” by using Confession, Emotion leakage, Physical control over the body, Apology, and Acting stupid. Finally, the FTAs enacted in the utterances of the main character are minimized by means of applying the politeness strategies. It has been discovered that the main character used the four types of politeness strategy that were positive politeness, negative politeness, bald on-record, and off-record strategy.